A Pain Management Decision Support System for Nurses - Heriot, Cathy (1988)
This paper describes the development and uses of the Nursing Pain Management Consultation System, a prototype demonstration project for Integrated Academic Information Management System (IAIMS) at the University of Utah. A knowledge base representing the best current thinking regarding management of acute pain secondary to total hip arthroplasty (THA) is the knowledge core of the expert system. The decisions modeled range from assessment of the severity of pain to decisions related to both pharmacologic and non-pharmacologic approaches to the alleviation of pain. The system also advises the nurses on measures to assess and prevent complications of the treatments.